Preaching the parables : from responsible interpretation to powerful proclamation - Blomberg, Craig L., 1955- (Grand Rapids, Mich. : Baker Academic, 2004)
Written with the rigor and precision of a New Testament specialist, Preaching the Parables provides a responsible introduction to understanding and proclaiming the parables that pastors, church leaders, and seminary students will appreciate. Craig Blomberg demonstrates how the structure of a parable is key to its interpretation and thus to its exposition. He shows how a parable, when properly contemporized, can be a powerful rhetorical device, and that recognizing the elements of the parable that were atypical to everyday life leads to important surprises that will be of significance to contemporary parishioners. Each of the fifteen exemplary sermons is accompanied by an analysis that points out key interpretive decisions
The parable of the prodigal sons and their father (Luke 15:11-32) -- Can I be saved without stewardship? (Luke 16:19-31) -- Who is my most important neighbor? (Luke 10:25-37) -- Can I be saved if I refuse to forgive others? (Matthew 18:23-35) -- Shrewd stewards (Luke 16:1-13) -- Let's play wedding, let's play funeral (Matthew 11:16-19) -- How do you hear? (Matthew 13:1-23) -- Seeds, weeds, and explosive growth (Matthew 13:24-43) -- The kingdom of heaven: priceless (Matthew 13:4-52) -- The basement of the Hard Rock Cafe (Matthew 7:13-27) -- The parable of the recovering homosexual (Luke 18:9-14) -- Pray and persevere (Luke 18:1-8) -- The cost of discipleship (Luke 14:25-35) -- How to prepare for Christ's return (Matthew 24:43-25:30) -- Who really are the sheep and the goats? (Matthew 25:31-46)
Includes bibliographical references (pages 221-238) and indexes
Keywords: Jesus Christ -- Parables -- Homiletical use; Jesus Christ -- Parables -- Sermons -- History and criticism; Jesus Christ -- Parables -- Sermons; Sermons, American -- History and criticism; Sermons, American